Second harmonic generation in a plexcitonic system comprising a quantum dot coupled to a reduced-symmetry plasmonic nanoparticle - Mina Rashidi; Nader Daneshfar (Results in Physics)
This paper theoretically investigates the nonlinear optical response of a heterodimer composed of a semiconductor quantum dot (QD) coupled with an eccentric metallic nanoshell that is commonly known as a nanoegg (NE). We study the SHG as the most common nonlinear optical process in a hybrid QD-NE system within the framework of the density matrix approach. We show that the presence of a nonconcentric plasmonic core–shell nanoparticle in the proximity of a QD strongly affects the intensity of the second harmonic signal emitted by the QD. In addition to the effect of the pump field intensity, the impact of the core offset, which is a result of the displacement of the center of the core from the shell of the nanoegg structure, on the second harmonic intensity of QD in the plexcitonic NE-QD system is shown and discussed. We also demonstrate how the size of the NE core and the shell thickness strongly affect the SHG intensity.